A case of generalized dermatosis - Fuyue TAN; Kunying QIN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
A 16-year-old male presented with dark-brown rashes on his torso and limbs for 10 years. Dermatological examination showed a large number of clusters of papules with dark brown grime like keratinous scales, size range from rice grains to mung beans on the torso and limbs. The skin was hard, dry and difficult to peel off. The boundaries were clear, and brown flaky scales were visible around. Supplementary examination: fungal smear (-), bran spores (-). Pathological examination showed mass or irregular hyperkeratosis of the epidermis, hair follicle horn thrombus, irregular thickening of the spinous layer, prolonged dermal process, increased melanin granules in the basal cell layer, and a small number of lymphocytes and histocytes around the superficial dermal vessels. Comprehensive clinical and pathological diagnosis of generalized skin scaling syndrome. After two weeks treatment with adapalene ointment, the primary lesions basically subsided, and the patient's condition was stable without recurrence.